Quotational higher-order thought theory. - Coleman, Sam (Philosophical Studies, 2015)
Due to their reliance on constitutive higher-order representing to generate the qualities of which the subject is consciously aware, I argue that the major existing higher-order representational theories of consciousness insulate us from our first-order sensory states. In fact on these views we are never properly conscious of our sensory states at all. In their place I offer a new higher-order theory of consciousness, with a view to making us suitably intimate with our sensory states in experience. This theory relies on the idea of 'quoting' sensory qualities, so is dubbed the 'quotational higher-order thought theory'. I argue that it can capture something of the idea that we are 'acquainted' with our conscious states without slipping beyond the pale for naturalists, whilst also providing satisfying treatments of traditional problems for higher-order theories concerning representational mismatch. The theory achieves this by abandoning a representational mechanism for mental intentionality, in favour of one based on 'embedding'.